Debris Emergence Elevations and Glacier Change - Shea, Joseph M.; Kraaijenbrink, Philip D. A.; Immerzeel, Walter W.; Brun, Fanny (Frontiers in Earth Science, 2021)
Debris-covered glaciers represent potentially significant stores of freshwater in river basins throughout High Mountain Asia (HMA). Direct glacier mass balance measurements are extremely difficult to maintain on debris-covered glaciers, and optical remote sensing techniques to evaluate annual equilibrium line altitudes (ELAs) do not work in regions with summer-accumulation type glaciers. Surface elevation and glacier velocity change have been calculated previously for debris-covered glaciers across the region, but the response of debris cover itself to climate change remains an open question. In this research we propose a new metric, i.e. the debris emergence elevation (ZDE), which can be calculated from a combination of optical and thermal imagery and digital elevation data. We quantify ZDE for 975 debris-covered glaciers in HMA over three compositing periods (1985-1999, 2000-2010, and 2013-2017) and compare ZDE against median glacier elevations, modelled ELAs, and observed rates of both mass change and glacier velocity change. Calculated values of ZDE for individual glaciers are broadly similar to both median glacier elevations and modelled ELAs, but slightly lower than both. Across the HMA region, the average value of ZDE increased by 70 +/- 126 m over the study period, or 2.7 +/- 4.1 m/yr. Increases in ZDE correspond with negative mass balance rates and decreases in glacier velocity, while glaciers and regions that show mass gains and increases in glacier velocity experienced decreases in ZDE. Regional patterns of ZDE , glacier mass balance, and glacier velocities are strongly correlated, which indicates continued overall increases in ZDEE and expansion of debris-covered areas as glaciers continue to lose mass. Our results suggest that ZDE is a useful metric to examine regional debris-covered glacier changes over decadal time scales, and could potentially be used to reconstruct relative mass and ELA changes on debris-covered glaciers using historical imagery or reconstructed debris cover extents.